Thor myth to Marvel - Arnold, Martin (Continuum, 2011)
"The myths of the Norse god Thor were preserved in the Icelandic Eddas, set down in the early Middle Ages. The bane of giants and trolls, Thor was worshipped as the last line of defence against all that threatened early Nordic society. Thor's significance persisted long after the Christian conversion and, in the mid-eighteenth century, Thor resumed a symbolic prominence among northern countries. Admired and adopted in Scandinavia and Germany, he became central to the rhetoric of national romanticism and to more belligerent assertions of nationalism. Resurrected in the latter part of the twentieth century in Marvel Magazine, Thor was further transformed into an articulation both of an anxious male sexuality and of a parallel nervousness regarding American foreign policy. Martin Arnold explores the extraordinary regard in which Thor has been held since medieval times and considers why and how his myth has been adopted, adapted and transformed"--Publisher's description
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references (p. [195]-215) and index
The Giant Killer : Thor in Old Norse mythology -- Theorizing Thor -- Christ versus Thor -- Recovering the Past : Scholarship from the Enlightenment to National Romanticism -- Thor in Denmark : From Klopstock to Grundtvig -- Thor in Germany : From Grimm to Himmler -- Thor in America : From Longfellow to Lee
Keywords: Donar; Geschichte; Thor (Norse deity); Sagengestalt; Mythologie; Literatur